Sodium fluoride (Na18F) PET Response Criteria in Solid Tumors (NAFCIST): a framework for response assessment in bone tumors - Kairemo, Kalevi; Gouda, M. A.; Buschhorn, Lars; Wahida, Adam; Macapinlac, H. A.; Anderson, P. M.; Subbiah, V. (ESMO open, 2023)
The current Response Evaluation Criteria in Solid Tumors for measuring tumor response in osteosarcoma may be sub-optimal, as even responsive bone tumors may show limited change in tumor diameters. This limits the use of traditional imaging assessment tools. Therefore, discerning osteosarcoma response to therapy on magnetic resonance imaging before surgery is often difficult, and it is typically evaluated after surgery by assessing the amount of necrosis in resected surgical specimens. To address these challenges, sodium fluoride (Na18F) positron emission tomography/computed tomography (PET/CT) scans can be utilized to better image bone response to therapy, as, fluoride is avidly taken up by bone. Na18F Response Criteria in Solid Tumors (NAFCIST) has been developed as a novel method to evaluate treatment response using Na18F PET/CT. Current evidence supporting NAFCIST comes from a pilot study that evaluated alpha particle radium-223 in patients with osteosarcoma. In this review, practical guidance for utilizing NAFCIST in the context of bone tumors is illustrated to aid future studies.
Online veröffentlicht am 28. Juli 2023
Im Titel erscheint die Zahl "18" hochgestellt
Gesehen am 06.12.2023